Secondary battery and electronic device including the same
By adjusting the ratio of ethyl propionate to propionate in the secondary battery electrolyte and adding vinylene carbonate and boron-containing lithium salt, a uniform solid electrolyte membrane is formed, which solves the problem of performance reduction under high temperature and high magnification conditions. , significantly improves the circulation and discharge performance of the secondary battery.
Patent Information
- Application Number
- CN202411094309.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2024-12-13
AI Technical Summary
Existing secondary batteries show reduced performance under high temperature and high magnification conditions, including increased gas production and reduced discharge capacity, mainly due to the damage to the solid electrolyte membrane on the surface of silicon carbon materials and the increase in internal impedance.
By adjusting the mass percentage ratio of ethyl propionate and propionate in the electrolyte solution, combining vinylene carbonate and boron-containing lithium salt, a uniform solid electrolyte membrane is formed, reducing side reactions and gas generation, and improving the negative electrode surface Wetting and kinetic properties.
The cycle characteristics and high-speed discharge characteristics of the secondary battery are significantly improved, the gas generation under high temperature and high magnification conditions is reduced, and the discharge performance and the overall performance of the battery are improved.
Smart Images

Figure CN119133608A_ABST
Abstract
Description
[0001] This application is a divisional application with application number 202410561295.3, application date 2024.05.08, application type invention, and application name “Secondary battery and electronic device containing the secondary battery”. Technical Field
[0002] The present application belongs to the field of electrochemical technology and relates to a secondary battery and an electronic device including the secondary battery. Background Art
[0003] Secondary batteries, such as lithium-ion batteries, have the advantages of being environmentally friendly, having high energy density, and having a long cycle life. They are widely used in mobile phones, computers, wearable devices, consumer drones, power tools, electric motorcycles, electric vehicles, or large energy storage devices. With the continuous expansion of the consumer market, the performance requirements for batteries are getting higher and higher. For example, secondary batteries need to maintain good performance under high and low temperature or high rate conditions. At present, carbonate compounds are often used as solvent systems for the electrolyte of secondary batteries, but this type of electrolyte is unstable under high rate conditions, which can easily cause the performance of secondary batteries to decrease. Summary of the invention
[0004] The purpose of the present application is to provide a secondary battery and an electrical device comprising the secondary battery. In the secondary battery provided in the present application, by improving the electrolyte system used, the gas generated by the secondary battery containing the electrolyte system at high temperature is reduced, and the high-rate discharge performance of the secondary battery is further improved.
[0005] According to a first aspect of the present application, the present application provides a secondary battery, the secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte;
[0006] The negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material;
[0007] The electrolyte comprises ethyl propionate and propyl propionate, and based on the total mass of the electrolyte, the mass percentage of the ethyl propionate is a%, and the mass percentage of the propyl propionate is b%, wherein 1.7≤a / b≤5.7;
[0008] The electrolyte further comprises at least one of vinylene carbonate, boron-containing lithium salt, and a compound having the structural formula shown in Formula I;
[0009]
[0010] Wherein, A in Formula I is selected from C2 to C5 alkylene.
[0011] After research, the present application found that when the electrolyte of a secondary battery contains ethyl propionate and propyl propionate in a specific ratio, the low-temperature performance of the secondary battery can be improved. However, under high temperature conditions, the defective structure on the surface of the silicon-carbon material of the secondary battery using silicon-carbon material as the negative electrode active material can easily cause uneven damage to the surface solid electrolyte membrane (SEI), thereby increasing the gas production inside the battery. When the secondary battery is discharged at a high rate, the internal impedance increases, the gas production further increases, and the discharge capacity decreases.
[0012] Based on this, the present application has found through research that in the electrolyte of a secondary battery with silicon-carbon material as the negative electrode active material, the mass percentage ratio a / b of ethyl propionate and propyl propionate is controlled to be in the range of 1.7 to 5.7, and when used in combination with at least one of vinylene carbonate, boron-containing lithium salt, and a compound containing the structural formula shown in Formula I, the surface wettability of the negative electrode silicon-carbon material under high temperature and high rate conditions can be significantly improved, a uniform SEI film can be formed on the surface of the silicon-carbon material, the electrode reaction on the negative electrode can be uniformly promoted, the gas generated under high temperature and high rate conditions can be reduced, the cycle characteristics and high-speed discharge characteristics of the secondary battery can be significantly improved, the lithium insertion and extraction on the negative electrode can be carried out uniformly, the reduction of discharge capacity during high-rate discharge can be effectively controlled, and the high-rate discharge performance of the secondary battery can be improved.
[0013] In some embodiments of the present application, the silicon-carbon material is prepared by mixing elemental silicon and graphite material or by depositing silicon with a porous carbon material as a skeleton; preferably, the silicon-carbon material is obtained by depositing silane with a porous carbon material as a skeleton; preferably, the preparation of the silicon-carbon material comprises the following steps: subjecting the porous carbon skeleton to a silane deposition reaction to obtain a precursor material, and micro-oxidizing the precursor material to obtain the silicon-carbon material.
[0014] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage ratio of the ethyl propionate to the propyl propionate is in the range of 3.1≤a / b≤4.9. The present application has found through research that when the mass percentage ratio of the ethyl propionate to the propyl propionate is further controlled within the above range, the gas generated under high temperature and high rate conditions can be more significantly reduced, and the cycle characteristics and high-rate discharge characteristics of the secondary battery can be significantly improved.
[0015] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the ethyl propionate is in the range of 20%≤a≤70%, and the mass percentage of the propyl propionate is in the range of 11%≤b≤20%; preferably, based on the total mass of the electrolyte, the mass percentage of the ethyl propionate is in the range of 36%≤a≤54%; and the mass percentage of the propyl propionate is in the range of 11%≤b≤15%. When the mass percentages of ethyl propionate and propyl propionate meet the above range characteristics, at this time, propyl propionate and ethyl propionate work together to make the electrolyte have a lower viscosity, and improve the softness of the SEI film at high temperature, form a more uniform SEI film on the surface of the silicon-carbon material, reduce the occurrence of side reactions, reduce the gas production of the secondary battery at high temperature, and improve the high-rate discharge performance of the secondary battery.
[0016] In some embodiments of the present application, based on the total mass of the electrolyte, the sum of the mass percentages of the ethyl propionate and the propyl propionate is in the range of 32%≤a+b≤84%; preferably, based on the total mass of the electrolyte, the sum of the mass percentages of the ethyl propionate and the propyl propionate is in the range of 47%≤a+b≤65%. When the sum of the mass percentages of the ethyl propionate and the propyl propionate meets the above range characteristics, the electrolyte can be ensured to have a lower viscosity, improve the dynamic performance inside the secondary battery, reduce the transfer impedance of active ions inside the secondary battery, reduce the gas generated by the secondary battery at high temperature, and improve the high-rate discharge performance of the secondary battery.
[0017] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage range of the ethyl propionate is: 20%≤a≤70%, the mass percentage range of the propyl propionate is: 11%≤b≤20%, and the sum of the mass percentages of the ethyl propionate and the propyl propionate satisfies 32%≤a+b≤84%; preferably, based on the total mass of the electrolyte, the mass percentage range of the ethyl propionate satisfies: 36%≤a≤54%, the mass percentage range of the propyl propionate is: 11%≤b≤15%, and the sum of the mass percentages of the ethyl propionate and the propyl propionate is in the range of 47%≤a+b≤65%.
[0018] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the compound containing the structural formula shown in Formula I is 0.11% to 4.9%; preferably, based on the total mass of the electrolyte, the mass percentage of the compound containing the structural formula shown in Formula I is 0.12% to 1.5%; more preferably, based on the total mass of the electrolyte, the mass percentage of the compound containing the structural formula shown in Formula I is 0.4% to 1.0%. More preferably, based on the total mass of the electrolyte, the mass percentage of the compound containing the structural formula shown in Formula I is 0.4% to 0.8%.
[0019] In some embodiments of the present application, the compound containing the structural formula shown in Formula I includes the compound shown in Formula II;
[0020]
[0021] Among them, by regulating the mass percentage of the compound containing the structural formula shown in Formula I within the above range, the compound containing the structural formula shown in Formula I can make the SEI film have a lower impedance, increase the insertion and extraction rate of active ions, and further improve the discharge performance of the secondary battery at a high rate.
[0022] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the vinylene carbonate is 0.01% to 0.3%; preferably, based on the total mass of the electrolyte, the mass percentage of the vinylene carbonate is 0.01% to 0.1%; preferably, based on the total mass of the electrolyte, the mass percentage of the vinylene carbonate is 0.01% to 0.06%.
[0023] In some embodiments of the present application, the electrolyte comprises vinylene carbonate and a boron-containing lithium salt, and based on the total mass of the electrolyte, the sum of the mass percentages of the vinylene carbonate and the boron-containing lithium salt is 0.04% to 0.2%; preferably, based on the total mass of the electrolyte, the sum of the mass percentages of the vinylene carbonate and the boron-containing lithium salt is 0.1% to 0.2%; preferably, based on the total mass of the electrolyte, the sum of the mass percentages of the vinylene carbonate and the boron-containing lithium salt is 0.1% to 0.16%.
[0024] In some embodiments of the present application, regulating the mass percentage of the vinyl carbonate within the above range can further promote the formation of a uniform low-impedance SEI film on the surface of the silicon-carbon material, reduce the gas generated inside the secondary battery, and improve the high-rate discharge performance of the secondary battery. Regulating the sum of the mass percentages of the vinyl carbonate and the boron-containing lithium salt within the above range can further promote the formation of a uniform SEI film on the surface of the silicon-carbon material, promote the uniform electrode reaction on the negative electrode, reduce the occurrence of side reactions, reduce the gas production inside the secondary battery, and make the viscosity of the electrolyte appropriate, thereby improving the cycle performance and high-rate discharge performance of the secondary battery.
[0025] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.01% to 0.25%; preferably, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.05% to 0.15%; more preferably, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.07% to 0.12%.
[0026] In some embodiments of the present application, the boron-containing lithium salt is selected from at least one of lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium borate.
[0027] Among them, in the technical solution provided in the present application, a boron-containing lithium salt is added to the electrolyte, and when the mass percentage of the boron-containing lithium salt is within the above range, it further promotes the formation of a uniform SEI film on the surface of the silicon-carbon material, reduces the impedance of the secondary battery, reduces the gas generated inside the secondary battery, and improves the cycle performance and high-rate discharge performance of the secondary battery. In particular, when lithium tetrafluoroborate is selected as the boron-containing lithium salt, the elasticity of the SEI film can be further improved, the active ion transfer impedance can be reduced, and the cycle performance and high-rate discharge performance of the secondary battery can be further improved.
[0028] In some embodiments of the present application, the electrolyte further comprises at least one of fluoroethylene carbonate, propylene carbonate and ethylene carbonate. The present application has found through research that when the electrolyte comprises at least one of fluoroethylene carbonate, propylene carbonate and ethylene carbonate, the internal dynamics of the secondary battery can be further improved, the active ion transmission can be promoted, and the high rate performance of the secondary battery can be improved.
[0029] In some embodiments of the present application, the mass percentage of the fluoroethylene carbonate is 2% to 7% based on the total mass of the electrolyte; preferably, the mass percentage of the fluoroethylene carbonate is 2.1% to 4.6% based on the total mass of the electrolyte. When the mass percentage of the fluoroethylene carbonate is adjusted within the above range, the high rate performance of the secondary battery can be further improved.
[0030] In some embodiments of the present application, the mass percentage of the propylene carbonate is 20% to 40% based on the total mass of the electrolyte; preferably, the mass percentage of the propylene carbonate is 20% to 35% based on the total mass of the electrolyte; preferably, the mass percentage of the propylene carbonate is 20% to 25% based on the total mass of the electrolyte. When the mass percentage of the propylene carbonate is adjusted within the above range, the high rate performance of the secondary battery can be further improved.
[0031] In some embodiments of the present application, the mass percentage of the ethylene carbonate is 4% to 18% based on the total mass of the electrolyte; preferably, the mass percentage of the ethylene carbonate is 11% to 16% based on the total mass of the electrolyte; preferably, the mass percentage of the ethylene carbonate is 11% to 14% based on the total mass of the electrolyte. When the mass percentage of the ethylene carbonate is regulated within the above range, the high rate performance of the secondary battery can be further improved.
[0032] In some embodiments of the present application, the electrolyte further comprises at least two of 1,3-propane sultone, succinonitrile, ethylene glycol bis(propionitrile) ether, and 1,3,6-hexane trinitrile. The present application has found through research that the above additives can improve the softness of SEI, and together with propyl propionate and ethyl propionate, improve the uniformity of SEI film formation on the surface of silicon-carbon material, reduce the occurrence of side reactions inside the battery, reduce the generation of gas at high temperature, reduce the internal impedance of the secondary battery, and further improve the high-rate discharge performance of the secondary battery.
[0033] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the 1,3-propane sultone is 0.1% to 4%; preferably, based on the total mass of the electrolyte, the mass percentage of the 1,3-propane sultone is 1.2% to 3.6%; preferably, based on the total mass of the electrolyte, the mass percentage of the 1,3-propane sultone is 2.0% to 3.0%. When the mass percentage of the 1,3-propane sultone is within the above range, the SEI film on the surface of the silicon-carbon material is more evenly distributed, which can further reduce the generation of gas at high temperature and improve the high-rate discharge performance of the secondary battery.
[0034] In some embodiments of the present application, the mass percentage of succinonitrile is 0.1% to 4% based on the total mass of the electrolyte; preferably, the mass percentage of succinonitrile is 1.6% to 2.4% based on the total mass of the electrolyte; preferably, the mass percentage of succinonitrile is 1.8% to 2.4% based on the total mass of the electrolyte. When the mass percentage of succinonitrile is adjusted within the above range, the SEI film on the surface of the silicon-carbon material has better softness, which can further reduce the generation of gas at high temperature and improve the high-rate discharge performance of the secondary battery.
[0035] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether is 0.01% to 1%; preferably, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether is 0.4% to 0.8%; preferably, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether is 0.5% to 0.8%. The SEI film on the surface of the silicon-carbon material has better uniformity, which can further reduce the generation of gas at high temperature and improve the high-rate discharge performance of the secondary battery.
[0036] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the 1,3,6-hexane trinitrile is 0.1% to 3.5%; preferably, based on the total mass of the electrolyte, the mass percentage of the 1,3,6-hexane trinitrile is 1.3% to 2.8%; preferably, based on the total mass of the electrolyte, the mass percentage of the 1,3,6-hexane trinitrile is 1.8% to 2.5%. When the mass percentage of the 1,3,6-hexane trinitrile is regulated within the above range, the transmission of active ions is promoted, the generation of gas at high temperature can be further reduced, and the high rate discharge performance of the secondary battery can be improved.
[0037] In some embodiments of the present application, the mass proportion of the silicon-carbon material in the negative electrode active material is 1% to 15%; preferably, the mass proportion of the silicon-carbon material in the negative electrode active material is 2% to 10%.
[0038] In some embodiments of the present application, based on the total mass of the electrolyte, when the mass percentage of the ethyl propionate is a%, the mass percentage of the propyl propionate is b%, 1.7≤a / b≤2.5, and the mass percentage range of the ethyl propionate is: 20%≤a≤30%, the mass percentage range of the propyl propionate is: 11%≤b≤15%, the mass percentage of the compound containing the structural formula shown in Formula I is 0.11% to 4.9%, and the mass percentage of the vinylene carbonate is 0.01% to 0.3%; or the boron-containing lithium salt The mass percentage content is 0.01% to 0.25%; or the mass percentage content of the fluoroethylene carbonate is 2% to 5%; or the mass percentage content of the propylene carbonate is 30% to 40%; or the mass percentage content of the ethylene carbonate is 8% to 14%; or the mass percentage content of the 1,3-propane sultone is 1.1% to 3.5%; or the mass percentage content of the succinonitrile is 1% to 4%; or the mass percentage content of the ethylene glycol bis(propionitrile) ether is 0.1% to 1%; or the mass percentage content of the 1,3,6-hexanetrinitrile is 0.5 to 3%.
[0039] In some embodiments of the present application, based on the total mass of the electrolyte, when the mass percentage of the ethyl propionate is a%, the mass percentage of the propyl propionate is b%, 1.9≤a / b≤2.2, and the mass percentage range of the ethyl propionate is: 20%≤a≤30%, the mass percentage range of the propyl propionate is: 11%≤b≤15%, the mass percentage of the compound containing the structural formula shown in Formula I is 0.11% to 1.0%, and the mass percentage of the vinylene carbonate is 0.01% to 0.1%; or the mass percentage of the boron-containing lithium salt is 0.11% to 1.0%. The mass percentage of the fluoroethylene carbonate is 0.05% to 0.2%; or the mass percentage of the fluoroethylene carbonate is 2% to 5%; or the mass percentage of the propylene carbonate is 30% to 40%; or the mass percentage of the ethylene carbonate is 8% to 14%; or the mass percentage of the 1,3-propane sultone is 1.1% to 3%; or the mass percentage of the succinonitrile is 1.1% to 3%; or the mass percentage of the ethylene glycol bis(propionitrile) ether is 0.1% to 0.8%; or the mass percentage of the 1,3,6-hexanetrinitrile is 0.7 to 2.5%.
[0040] In some embodiments of the present application, the negative electrode active material further includes graphite, a conductive agent, and a binder.
[0041] According to a second aspect of the present application, the present application provides an electronic device, wherein the electronic device comprises a secondary battery as described in any one of the first aspects of the present application.
[0042] Compared with the prior art, this application has the following beneficial effects:
[0043] The present application provides a secondary battery. In the electrolyte of the secondary battery using silicon-carbon material as the negative electrode active material, by controlling the mass percentage ratio a / b of ethyl propionate and propyl propionate to be in the range of 1.7 to 5.7, and using them in combination with at least one of vinylene carbonate, boron-containing lithium salt, and a compound having the structural formula shown in Formula I, under high temperature and high rate conditions, the surface wettability of the negative electrode silicon-carbon material can be improved, a uniform SEI film can be formed on the surface of the silicon-carbon material, the electrode reaction on the negative electrode can be uniformly promoted, the gas generated under high temperature and high rate conditions can be reduced, the cycle characteristics and high-speed discharge characteristics of the secondary battery can be significantly improved, the lithium insertion and extraction on the negative electrode can be uniformly carried out, the reduction of discharge capacity during high-rate discharge can be effectively controlled, and the high-rate discharge performance of the secondary battery can be improved. DETAILED DESCRIPTION
[0044] The technical solution of the present application is further described below through specific embodiments, which do not limit the protection scope of the present application. Some non-essential modifications and adjustments made by others based on the concept of the present application still fall within the protection scope of the present application.
[0045] It should be noted that in the following content, lithium-ion batteries are used as an example of secondary batteries to explain the present application, but the secondary batteries of the present application are not limited to lithium-ion batteries, but can also be any other suitable secondary batteries, such as lithium metal secondary batteries, lithium polymer secondary batteries or lithium ion polymer secondary batteries, etc.
[0046] According to a first aspect of the present application, the present application provides a secondary battery, the secondary battery comprising a positive electrode, a negative electrode, a separator and an electrolyte; the negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, the negative electrode active material comprises a silicon-carbon material; the electrolyte comprises a non-aqueous solvent and a boron-containing lithium salt, the non-aqueous solvent comprises ethyl propionate and propyl propionate, based on the total mass of the electrolyte, the mass percentage of ethyl propionate is a%, the mass percentage of propyl propionate is b%, wherein 1.7≤a / b≤5.7;
[0047] The electrolyte further comprises at least one of vinylene carbonate, boron-containing lithium salt, and a compound having the structural formula shown in Formula I;
[0048]
[0049] Wherein, A in Formula I is selected from C2 to C5 alkylene.
[0050] After research, the present application found that when the electrolyte of a secondary battery contains ethyl propionate and propyl propionate in a specific ratio, the low-temperature performance of the secondary battery can be improved. However, under high temperature conditions, the defective structure on the surface of the silicon-carbon material of the secondary battery using silicon-carbon material as the negative electrode active material can easily cause uneven damage to the surface solid electrolyte membrane (SEI), thereby increasing the gas production inside the battery. When the secondary battery is discharged at a high rate, the internal impedance increases, the gas production further increases, and the discharge capacity decreases.
[0051] Therefore, in the electrolyte of a secondary battery using silicon-carbon material as the negative electrode active material, the mass percentage ratio a / b of ethyl propionate and propyl propionate is controlled to be in the range of 1.7 to 5.7, and is used in combination with at least one of vinylene carbonate, boron-containing lithium salt, and a compound having the structural formula shown in Formula I. This can significantly improve the surface wettability of the negative electrode silicon-carbon material under high temperature and high rate conditions, form a uniform SEI film on the surface of the silicon-carbon material, promote uniform electrode reaction on the negative electrode, reduce the gas generated under high temperature and high rate conditions, significantly improve the cycle characteristics and high-speed discharge characteristics of the secondary battery, enable the lithium insertion and extraction on the negative electrode to proceed uniformly, effectively control the reduction in discharge capacity during high-rate discharge, and improve the high-rate discharge performance of the secondary battery.
[0052] In some embodiments of the present application, the silicon-carbon material can be prepared by mixing a single silicon material and a graphite material, or by using a porous carbon material as a skeleton and then depositing silicon; preferably, the silicon-carbon material is prepared by using a porous carbon material as a skeleton and then depositing silane. Preferably, the preparation of the silicon-carbon material comprises the following steps: subjecting the porous carbon skeleton to a silane deposition reaction to obtain a precursor material, and micro-oxidizing the precursor material to obtain the silicon-carbon material.
[0053] Specifically, in some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage ratio of ethyl propionate to propyl propionate can be 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7 or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage ratio of ethyl propionate to propyl propionate can be 1.9 to 5.4, 2.1 to 5.6, 2.5 to 5.0, 3.2 to 5.4 or 2.3 to 4.8. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage ratio of ethyl propionate to propyl propionate is preferably in the range of 3.1≤a / b≤4.9. The present application has found that when the mass percentage ratio of ethyl propionate to propyl propionate is further controlled within the above range, the gas generated under high temperature and high rate conditions can be more significantly reduced, and the cycle characteristics and high-speed discharge characteristics of the secondary battery can be significantly improved.
[0054] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage content of ethyl propionate ranges from 20%≤a≤70%; preferably, the mass percentage content of ethyl propionate ranges from 36%≤a≤54%. Specifically, the mass percentage of ethyl propionate can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 65%, 66%, 67%, 68%, 69%, 70% or the scope composed of any two of the above numerical values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of ethyl propionate may range from 25% to 57%, 28% to 62%, 30% to 55%, 32% to 58% or 34% to 56%.
[0055] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of propyl propionate ranges from 11% ≤ b ≤ 20%; preferably, based on the total mass of the electrolyte, the mass percentage of propyl propionate ranges from 11% ≤ b ≤ 15%. Specifically, the mass percentage of propyl propionate can be 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of propyl propionate can be 12% to 18%, 13% to 19% or 14% to 18%.
[0056] When the mass percentages of ethyl propionate and propyl propionate meet the above-mentioned range characteristics, at this time, propyl propionate and ethyl propionate working together can further make the electrolyte have a lower viscosity, and further improve the softness of the SEI film at high temperature, form a more uniform SEI film on the surface of the silicon-carbon material, further reduce the occurrence of side reactions, reduce the gas production of the secondary battery at high temperature, and further improve the high-rate discharge performance of the secondary battery.
[0057] In some embodiments of the present application, based on the total mass of the electrolyte, the sum of the mass percentages of ethyl propionate and propyl propionate ranges from 32% ≤ a + b ≤ 84%. Preferably, based on the total mass of the electrolyte, the sum of the mass percentages of ethyl propionate and propyl propionate ranges from 47% ≤ a + b ≤ 65%. In some embodiments of the present application, based on the total mass of the electrolyte, the sum of the mass percentages of ethyl propionate and propyl propionate can be 35% to 70%, 38% to 73%, 41% to 75% or 44% to 64%. When the sum of the mass percentages of ethyl propionate and propyl propionate further meets the above range characteristics, it can further ensure that the electrolyte has a lower viscosity, improve the dynamic performance inside the secondary battery, reduce the internal active ion transfer impedance of the secondary battery, and more significantly reduce the gas generated by the secondary battery at high temperature, thereby improving the high rate discharge performance of the secondary battery.
[0058] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of ethyl propionate and propyl propionate satisfies the range of 20%≤a≤70%, 11%≤b≤20%, and the sum of the mass percentage of ethyl propionate and propyl propionate satisfies the range of 32%≤a+b≤84%. Preferably, based on the total mass of the electrolyte, the mass percentage of ethyl propionate and propyl propionate satisfies the range of 36%≤a≤54%, 11%≤b≤15%, and the sum of the mass percentage of ethyl propionate and propyl propionate satisfies the range of 47%≤a+b≤65%.
[0059] In some embodiments of the present application, the mass percentage of the compound containing the structural formula shown in Formula I is 0.11% to 4.9% based on the total mass of the electrolyte. Preferably, the mass percentage of the compound containing the structural formula shown in Formula I is 0.12% to 1.5% based on the total mass of the electrolyte; more preferably, the mass percentage of the compound containing the structural formula shown in Formula I is 0.4% to 1.0% based on the total mass of the electrolyte. More preferably, the mass percentage of the compound containing the structural formula shown in Formula I is 0.4% to 0.8% based on the total mass of the electrolyte. Specifically, based on the total mass of the electrolyte, the mass percentage of the compound containing the structural formula shown in Formula I can be 0.11%, 0.15%, 0.17%, 0.19%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 4.6%, 4.7%, 4.8%, 4.9% or a range composed of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the compound containing the structural formula shown in Formula I can be 0.2% to 0.9%, 0.15% to 1.2% or 0.3% to 0.8%.
[0060] In some embodiments of the present application, the compound containing the structural formula shown in Formula I includes the compound shown in Formula II;
[0061]
[0062] Among them, by regulating the mass percentage of the compound containing the structural formula shown in Formula I within the above range, the compound containing the structural formula shown in Formula I can further make the SEI film have a lower impedance, increase the insertion and extraction rate of active ions, and further improve the discharge performance of the secondary battery at a high rate.
[0063] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of vinylene carbonate is 0.01% to 0.3%; preferably, based on the total mass of the electrolyte, the mass percentage of vinylene carbonate is 0.01% to 0.1%; preferably, based on the total mass of the electrolyte, the mass percentage of vinylene carbonate is 0.01% to 0.06%. Specifically, based on the total mass of the electrolyte, the mass percentage of vinylene carbonate can be 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.25%, 0.26%, 0.27%, 0.28%, 0.29%, 0.3% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of vinylene carbonate can be 0.02% to 0.11%, 0.03% to 0.14% or 0.01% to 0.09%. When the mass percentage of vinylene carbonate is within the above range, it can further promote the formation of a uniform SEI film on the surface of the silicon-carbon material, more significantly reduce the gas generated inside the secondary battery, and improve the high-rate discharge performance of the secondary battery.
[0064] In some embodiments of the present application, the electrolyte comprises vinylene carbonate and a boron-containing lithium salt, and the sum of the mass percentages of vinylene carbonate and the boron-containing lithium salt is 0.04% to 0.2% based on the total mass of the electrolyte; preferably, the sum of the mass percentages of vinylene carbonate and the boron-containing lithium salt is 0.1% to 0.2% based on the total mass of the electrolyte; preferably, the sum of the mass percentages of vinylene carbonate and the boron-containing lithium salt is 0.1% to 0.16% based on the total mass of the electrolyte. Specifically, based on the total mass of the electrolyte, the sum of the mass percentages of vinylene carbonate and boron-containing lithium salt can be 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2% or a range consisting of any two of the above numerical values. In some embodiments of the present application, based on the total mass of the electrolyte, the sum of the mass percentages of vinylene carbonate and boron-containing lithium salt can be 0.08% to 0.18%, 0.06% to 0.15% or 0.05% to 0.17%. When the electrolyte contains both vinylene carbonate and boron-containing lithium salt and the sum of the mass percentages of vinylene carbonate and lithium tetrafluoroborate satisfies the above relationship, it can further promote the formation of a uniform SEI film on the surface of the silicon-carbon material, promote the uniform electrode reaction on the negative electrode, reduce the occurrence of side reactions, reduce gas production inside the secondary battery, and make the viscosity of the electrolyte appropriate, thereby significantly improving the high-rate discharge performance of the secondary battery.
[0065] In some embodiments of the present application, the boron-containing lithium salt is selected from at least one of lithium difluorooxalate borate, lithium tetrafluoroborate, and lithium borate. Preferably, the boron-containing lithium salt is selected from lithium tetrafluoroborate. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.01% to 0.25%; preferably, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.05% to 0.15%; more preferably, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt is 0.07% to 0.12%. Specifically, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.15%, 0.2%, 0.21%, 0.22%, 0.23%, 0.24%, 0.25% or a range composed of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of the boron-containing lithium salt can be 0.03% to 0.13% or 0.06% to 0.14%. Adding a boron-containing lithium salt to the electrolyte, and when the mass percentage of the boron-containing lithium salt is within the above range, further promotes the formation of a uniform SEI film on the surface of the silicon-carbon material, reduces the impedance of the secondary battery, and more significantly reduces the gas generated inside the secondary battery, and improves the high-rate discharge performance of the secondary battery.
[0066] In some embodiments of the present application, the electrolyte further comprises at least one of fluoroethylene carbonate, propylene carbonate and ethylene carbonate. When the electrolyte comprises at least one of fluoroethylene carbonate, propylene carbonate and ethylene carbonate, the internal dynamics of the secondary battery can be further improved, the active ion transport can be promoted, and the high rate performance of the secondary battery can be more significantly improved.
[0067] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 2% to 7%; preferably, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate is 2.1% to 4.6%. Specifically, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate can be 2%, 3%, 4%, 5%, 6%, 7% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of fluoroethylene carbonate can be 2.4% to 5.2%, 2.7% to 5.6%, 2.3% to 6.0% or 2.2% to 5.4%. When the mass percentage of fluoroethylene carbonate is in the above range, the high rate performance of the secondary battery can be further improved.
[0068] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of propylene carbonate is 20% to 40%; preferably, based on the total mass of the electrolyte, the mass percentage of propylene carbonate is 20% to 35%; preferably, based on the total mass of the electrolyte, the mass percentage of propylene carbonate is 20% to 25%. Specifically, based on the total mass of the electrolyte, the mass percentage of propylene carbonate can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of propylene carbonate can be 22% to 37%, 21% to 33% or 20% to 31%. When the mass percentage of propylene carbonate is in the above range, the high rate performance of the secondary battery can be further improved.
[0069] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of ethylene carbonate is 4% to 18%; preferably, based on the total mass of the electrolyte, the mass percentage of ethylene carbonate is 11% to 16%; preferably, based on the total mass of the electrolyte, the mass percentage of ethylene carbonate is 11% to 14%. Specifically, based on the total mass of the electrolyte, the mass percentage of ethylene carbonate can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of ethylene carbonate can be 5% to 15% or 7% to 17%. When the mass percentage of ethylene carbonate is in the above range, the high rate performance of the secondary battery can be further improved.
[0070] In some embodiments of the present application, the electrolyte further comprises at least two of 1,3-propane sultone, succinonitrile, ethylene glycol bis(propionitrile) ether, and 1,3,6-hexane trinitrile. The above additives can improve the softness of SEI, and together with propyl propionate and ethyl propionate, improve the uniformity of SEI film formation on the surface of silicon-carbon material, reduce the occurrence of side reactions inside the battery, reduce the generation of gas at high temperature, reduce the internal impedance of the secondary battery, and further improve the high-rate discharge performance of the secondary battery.
[0071] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of 1,3-propane sultone is 0.1% to 4%; preferably, based on the total mass of the electrolyte, the mass percentage of 1,3-propane sultone is 1.2% to 3.6%; preferably, based on the total mass of the electrolyte, the mass percentage of 1,3-propane sultone is 2.0% to 3.0%. Specifically, based on the total mass of the electrolyte, the mass percentage of 1,3-propane sultone can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3%, 3.5%, 4% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of 1,3-propane sultone can be 0.4% to 3.3%, 0.8% to 3.1% or 1.4% to 3.4%. When the mass percentage of 1,3-propane sultone is within the above range, the generation of gas at high temperature can be further reduced and the high rate discharge performance of the secondary battery can be improved.
[0072] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of succinonitrile is 0.1% to 4%; preferably, based on the total mass of the electrolyte, the mass percentage of succinonitrile is 1.6% to 2.4%. Specifically, based on the total mass of the electrolyte, the mass percentage of succinonitrile can be 0.1%, 0.15%, 0.2%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexanetrinitrile can be 0.2% to 2.5%, 0.5% to 2.7%, 0.8% to 2.9%, 1.1% to 3.4% or 0.9% to 2.8%. When the mass percentage of succinonitrile is within the above range, the generation of gas at high temperature can be further reduced and the high rate discharge performance of the secondary battery can be improved.
[0073] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether is 0.01% to 1%; preferably, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether can be 0.4% to 0.8%. Specifically, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether can be 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis (propionitrile) ether can be 0.15% to 1.5%, 0.2% to 1.2% or 0.3% to 1.0%. When the mass percentage of ethylene glycol bis (propionitrile) ether is within the above range, the generation of gas at high temperature can be further reduced and the high rate discharge performance of the secondary battery can be improved.
[0074] In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexane trinitrile is 0.1% to 3.5%; preferably, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexane trinitrile is 1.3% to 2.8%; preferably, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexane trinitrile is 1.8% to 2.5%. Specifically, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexane trinitrile can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5% or a range consisting of any two of the above values. In some embodiments of the present application, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexane trinitrile can be 0.2% to 2.5%, 0.5% to 2.7%, 0.8% to 2.9%, 1.1% to 3.4% or 0.9% to 2.8%. When the mass percentage of 1,3,6-hexane trinitrile is within the above range, the generation of gas at high temperature can be further reduced and the high rate discharge performance of the secondary battery can be improved.
[0075] In some embodiments of the present application, based on the total mass of the electrolyte, when the mass percentage of ethyl propionate is a%, the mass percentage of propyl propionate is b%, 1.7≤a / b≤2.5, and the mass percentage range of ethyl propionate is: 20%≤a≤30%, the mass percentage range of propyl propionate is: 11%≤b≤15%, the mass percentage of the compound containing the structural formula shown in Formula I is 0.11% to 4.9%, and the mass percentage of vinylene carbonate is 0.01% to 0.3%; or the mass percentage of boron-containing lithium salt is 0.11% to 4.9%, and the mass percentage of vinylene carbonate is 0.01% to 0.3%; or the mass percentage of boron-containing lithium salt is 0.11% to 4.9%, and the mass percentage of propyl propionate is 0.01% to 0.3%; The mass percentage of ethylene carbonate is 0.01% to 0.25%; or the mass percentage of fluoroethylene carbonate is 2% to 5%; or the mass percentage of propylene carbonate is 30% to 40%; or the mass percentage of ethylene carbonate is 8% to 14%; or the mass percentage of 1,3-propane sultone is 1.1% to 3.5%; or the mass percentage of succinonitrile is 1% to 4%; or the mass percentage of ethylene glycol bis(propionitrile) ether is 0.1% to 1%; or the mass percentage of 1,3,6-hexanetrinitrile is 0.5 to 3%.
[0076] In some embodiments of the present application, based on the total mass of the electrolyte, when the mass percentage of ethyl propionate is a%, the mass percentage of propyl propionate is b%, 1.9≤a / b≤2.2, and the mass percentage range of ethyl propionate is: 20%≤a≤30%, the mass percentage range of propyl propionate is: 11%≤b≤15%, the mass percentage of the compound containing the structural formula shown in Formula I is 0.11% to 1.0%, the mass percentage of vinylene carbonate is 0.01% to 0.1%; or the mass percentage of boron-containing lithium salt is The content of ethylene carbonate is 0.05% to 0.2% by weight; or the mass percentage of fluoroethylene carbonate is 2% to 5%; or the mass percentage of propylene carbonate is 30% to 40%; or the mass percentage of ethylene carbonate is 8% to 14%; or the mass percentage of 1,3-propane sultone is 1.1% to 3%; or the mass percentage of succinonitrile is 1.1% to 3%; or the mass percentage of ethylene glycol bis(propionitrile) ether is 0.1% to 0.8%; or the mass percentage of 1,3,6-hexanetrinitrile is 0.7 to 2.5%.
[0077] In some embodiments of the present application, the electrolyte provided by the present application may further include some other components, which may include but are not limited to: diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or dimethyl carbonate (DMC). In some embodiments of the present application, other components may include ether solvents, which may include but are not limited to: at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME).
[0078] In some embodiments of the present application, the electrolyte provided in the present application may also include a lithium salt as an electrolyte. The lithium salt in the electrolyte includes, but is not limited to: LiClO4, LiAsF6, LiPF6, LiSbF6, LiSO3F, LiN(FSO2)2, LiCF3SO3, LiN(FSO2)(CF3SO2), LiN(CF3SO2)2, LiN(C2F5SO2)2, lithium bis(oxalate)borate, lithium tris(oxalate)phosphate, lithium difluorobis(oxalate)phosphate or lithium tetrafluoro(oxalate)phosphate. In addition, the above-mentioned lithium salts can be used alone or in combination of two or more. In some embodiments, the lithium salt includes LiPF6. In some embodiments, based on the total mass of the electrolyte, the mass percentage of the lithium salt in the electrolyte is 10% to 20%. Specifically, based on the total mass of the electrolyte, the mass percentage of lithium salt in the electrolyte is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% or a range consisting of any two of the above values.
[0079] In some embodiments of the present application, the preparation method of the electrolyte provided in the present application is not limited, and can be prepared in the manner of a conventional electrolyte. In some embodiments, the electrolyte of the present application can be prepared by mixing the components.
[0080] In some embodiments of the present application, the mass proportion of silicon-carbon material in the negative electrode active material is 1 to 15% in the negative electrode active material; preferably, the mass proportion of silicon-carbon material in the negative electrode active material is 2 to 10%. Specifically, the mass proportion of silicon-carbon material in the negative electrode active material is 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or a range consisting of any two of the above values.
[0081] In some embodiments of the present application, the negative electrode active material further comprises graphite, and the graphite comprises at least one of artificial graphite or natural graphite.
[0082] In some embodiments of the present application, the negative electrode active material also includes a binder, which may include various binder polymers such as polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc.
[0083] In some embodiments of the present application, the negative electrode active material further comprises a conductive agent to improve the electrode conductivity. Any conductive material can be used as the conductive material as long as it does not cause chemical changes. Examples of conductive agents include, but are not limited to: carbon-based materials, such as carbon black, acetylene black, Ketjen black, carbon fibers, etc.; metal-based materials, such as metal powders or metal fibers including copper, nickel, aluminum, silver, etc.; conductive polymers, such as polyphenylene derivatives, etc.; or mixtures thereof.
[0084] In some embodiments of the present application, in the negative electrode active material, the weight ratio of the silicon-carbon material to the graphite, the conductive agent and the binder is 1-15:80-95:0.5-2:1-3.
[0085] In some embodiments of the present application, the negative electrode further comprises a negative electrode current collector, and the negative electrode current collector includes, but is not limited to: copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate covered with a conductive metal, and any combination thereof. In some embodiments, the negative electrode current collector is copper foil.
[0086] In some embodiments of the present application, the structure of the negative electrode may be a negative electrode structure known in the art that can be used in an electrochemical device.
[0087] In some embodiments of the present application, the preparation method of the negative electrode is a method for preparing a negative electrode that can be used for an electrochemical device that is well known in the art. Exemplarily, the negative electrode can be obtained by the following method: mixing a negative electrode active material, a conductive agent, and a binder in a solvent, and heating a thickener as needed to prepare a negative electrode active material slurry, and coating the negative electrode active material slurry on a negative electrode current collector, drying, and cold pressing to form a negative electrode active material layer. In some embodiments, the solvent may include, but is not limited to, water, N-methylpyrrolidone.
[0088] In some embodiments of the present application, the positive electrode of the secondary battery includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector. The specific types of positive electrode active materials of the positive electrode active material layer are not subject to specific restrictions and can be selected according to needs. In some embodiments of the present application, the positive electrode active material includes a lithium transition metal composite oxide. In some embodiments, the positive electrode active material is selected from at least one of the following: lithium cobalt oxide (LiCoO2), lithium nickel manganese cobalt ternary material (NCM), lithium manganese oxide (LiMn2O4), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4) or lithium iron phosphate (LiFePO4).
[0089] In some embodiments of the present application, the positive electrode active material layer also includes a binder, and optionally also includes a conductive material. The binder can improve the bonding between the positive electrode active material particles, and can improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, the binder includes, but is not limited to, polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin and nylon, etc.
[0090] In some embodiments of the present application, the positive electrode active material layer also includes a conductive material to impart conductivity to the electrode. The conductive material may include any conductive material as long as it does not cause chemical changes. Non-limiting examples of conductive materials include carbon-based materials (e.g., carbon black, acetylene black, Ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof.
[0091] In some embodiments of the present application, the positive electrode current collector is a metal, such as aluminum foil.
[0092] In some embodiments of the present application, the structure of the positive electrode is a positive electrode structure known in the art and can be used in a secondary battery.
[0093] In some embodiments of the present application, the preparation method of the positive electrode is a preparation method of the positive electrode that can be used for a secondary battery that is well known in the art. For example, the positive electrode can be obtained by the following method: a positive electrode active material, a conductive material, and a binder are mixed in a solvent to prepare a positive electrode active material slurry, and the positive electrode active material slurry is coated on a positive electrode current collector, dried, and cold pressed to form a positive electrode active material layer. In some embodiments, the solvent may include water, N-methylpyrrolidone, etc., but is not limited thereto.
[0094] In some embodiments of the present application, the separator of the secondary battery is used to prevent short circuit. The material and shape of the separator are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic material formed by a material that is stable to the electrolyte of the present application. For example, in some embodiments, the separator includes a substrate layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure. The material of the substrate layer can be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, the material of the substrate layer can be selected from at least one of a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film. A surface treatment layer is provided on at least one surface of the substrate layer. The surface treatment layer can be a polymer layer, an inorganic layer or a layer formed by a mixed polymer and an inorganic material. Specifically, the inorganic layer includes inorganic particles and a binder. The inorganic particles may be selected from one or a combination of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The binder may be selected from one or a combination of polyvinylidene fluoride, a polymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0095] In some embodiments of the present application, the secondary battery of the present application includes, but is not limited to: a lithium ion battery or a sodium ion battery. In some embodiments of the present application, the secondary battery includes a lithium ion battery.
[0096] According to the second aspect of the present application, the present application provides an electronic device, the electronic device includes a secondary battery as any embodiment of the first aspect of the present application. In some embodiments, the present application does not particularly limit the use of the secondary battery, and it can be used for any electrical device or equipment known in the prior art. For example, the electronic device includes, but is not limited to, a laptop computer, a pen input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium ion capacitor, etc. In addition, the secondary battery provided in the present application is applicable to energy storage power stations, marine vehicles, and air vehicles in addition to the electronic devices listed above. The air vehicle includes an air vehicle in the atmosphere and an air vehicle outside the atmosphere.
[0097] Example
[0098] Hereinafter, the present application will be described in more detail by using specific examples and comparative examples.
[0099] The test methods used in the following examples and comparative examples are as follows:
[0100] 1. Electrolyte testing
[0101] The components and their contents in the electrolyte can be determined by conventional methods in the art. For example, the components and their contents in the electrolyte can be detected by gas chromatography-mass spectrometry (GC-MS), ion chromatography (IC), liquid chromatography (LC), etc.
[0102] 2. Performance test of lithium-ion batteries
[0103] 2.1 Gas generation
[0104] The lithium-ion battery was charged at 1C constant current and constant voltage at 25°C until the end voltage was 4.4V, and then charged at a constant voltage of 4.4V for 5h; then discharged at a current of 0.3C to a end voltage of 3.0V, and the above charge and discharge cycles were performed 5 times, and charged at a constant current of 0.3C to 4.4V at a high temperature (70°C), and kept at a constant voltage of 4.4V for 5 days. The gas generation after 5 days of storage was measured by the Archimedean method. The gas generation was calculated by setting the gas generation of Comparative Example 1-1 to 100% as a benchmark to obtain the relative gas generation.
[0105] 2.2 High rate discharge capacity ratio
[0106] Test process: Charge the lithium-ion battery to 4.4V at 500mA, then discharge it to 3.0V at 500mA, and get the discharge capacity C0 of the lithium-ion battery; in addition, charge the lithium-ion battery to 4.4V at 500mA, then discharge it to 3.0V at 3A, and get the discharge capacity C1 of the lithium-ion battery. High-rate discharge capacity ratio = C1 / C2.
[0107] Example 1-1
[0108] 1. Preparation of negative electrode
[0109] Preparation of silicon carbon materials:
[0110] Take a porous carbon skeleton: the pore volume of the porous carbon skeleton is 0.65g / cc, of which the pore volume of micropores and mesopores is 80%; carry out a silane deposition reaction on the porous carbon skeleton, and the conditions of the silane deposition reaction include: at 650°C, introduce silane gas with a volume content of 22%, and other gas components are nitrogen, and the reaction time is 9h to obtain a precursor material, and at 100°C, introduce oxygen with a volume content of 20%, and other gas components are nitrogen, and the reaction time is 14h to obtain a silicon-carbon material.
[0111] The silicon-carbon material, artificial graphite, conductive agent carbon black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) prepared above are added to deionized water in a mass ratio of 5:90:1.5:2:1.5, and stirred and mixed to form a uniform negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried, and cold pressed to form a negative electrode active material layer, and then cut into pieces and welded to the pole ears to obtain the negative electrode.
[0112] 2. Preparation of positive electrode
[0113] The positive electrode active material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are mixed in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 96.3:2.2:1.5, and fully stirred in a vacuum mixer to obtain a positive electrode slurry. The positive electrode material is coated on the positive electrode current collector aluminum foil, dried, and cold pressed to form a positive electrode active material layer, and then cut into pieces and welded to the pole ears to obtain the positive electrode.
[0114] 3. Preparation of electrolyte
[0115] In a dry argon atmosphere glove box, propyl propionate (PP), ethyl propionate (EP), and diethyl carbonate (DEC) are mixed evenly, dissolved and fully stirred, and then lithium salt LiPF6, lithium tetrafluoroborate, vinylene carbonate and compound of formula II are added, and the electrolyte is obtained after mixing evenly. Among them, based on the total mass of the electrolyte, the mass percentage of ethyl propionate is 49%, the mass percentage of propyl propionate is 12.0%, the mass percentage of vinylene carbonate is 0.03%, the mass percentage of lithium tetrafluoroborate is 0.1%, the mass percentage of compound of formula II is 0.65%, the lithium salt LiPF6 is 12%, and the balance is diethyl carbonate.
[0116] 4. Preparation of isolation membrane
[0117] A polyethylene (PE) porous polymer film is used as the isolation membrane.
[0118] 5. Preparation of lithium-ion batteries
[0119] The prepared positive electrode, isolation film, and negative electrode are stacked in order, so that the isolation film is placed between the positive electrode and the negative electrode to play an isolating role, and then wound to obtain a bare cell; the bare cell is placed in an outer packaging foil aluminum-plastic film, and the electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation and other process flows.
[0120] Examples 1-2 to 1-33, Comparative Examples 1-1 to 1-7
[0121] Referring to the preparation method of the electrolyte and lithium ion battery of Example 1-1, the differences from Example 1-1 are detailed in the data of Table 1.
[0122] Examples 1-34
[0123] This embodiment is based on Embodiment 1-1, and differs from Embodiment 1-1 in that lithium tetrafluoroborate in the electrolyte is replaced with lithium difluorooxalatoborate, and the rest is the same as Embodiment 1-1.
[0124] Comparative Examples 1-8
[0125] This comparative example is based on Example 1-1, and the difference from Example 1-1 is that the preparation method of the negative electrode is changed, and the silicon-carbon material in the negative electrode preparation step of Example 1-1 is replaced with artificial graphite. The specific steps of preparing the negative electrode are as follows:
[0126] Artificial graphite, conductive agent carbon black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) are added to the solvent deionized water in a mass ratio of 95:1.5:2:1.5 and stirred thoroughly to form a uniform negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, dried, and cold pressed to form a negative electrode active material layer, and then cut into pieces and welded to the pole ears to obtain the negative electrode.
[0127] In Table 1, the mass percentage of ethyl propionate is a%, the mass percentage of propyl propionate is b%, the mass percentage of vinylene carbonate is c%, the mass percentage of lithium tetrafluoroborate (or lithium difluorooxalatoborate) is d%, the mass percentage of the compound of formula II is e%, the mass percentage ratio of ethyl propionate to propyl propionate in the electrolyte is a / b, the sum of the mass percentages of ethyl propionate and propyl propionate in the electrolyte is (a+b)%, and the sum of the mass percentages of vinylene carbonate and lithium tetrafluoroborate in the electrolyte is (c+d)%.
[0128] Table 1
[0129]
[0130]
[0131] According to the results presented in Table 1 above, in the electrolyte of a secondary battery using a silicon-carbon material as a negative electrode active material, when the mass percentage ratio a / b of ethyl propionate and propyl propionate is controlled within a certain range and used in combination with at least one of vinylene carbonate, boron-containing lithium salt, and the compound of formula II, the high-rate discharge capacity ratio under high temperature and high-rate conditions can be significantly improved, and the gas generated under high temperature and high-rate conditions can be reduced.
[0132] Based on the results in Table 1 above, the effects of other components and dosages on the high-temperature gas generation and high-rate discharge capacity performance of lithium-ion batteries are further explored, as shown in Table 2:
[0133] Table 2
[0134]
[0135]
[0136]
[0137] It can be seen from Table 2 that when the electrolyte contains at least one of fluoroethylene carbonate, propylene carbonate or ethylene carbonate, the generation of gas at high temperature of the lithium-ion battery is further reduced, and the high-rate discharge performance is further improved. When the electrolyte contains at least two of 1,3-propane sultone, succinonitrile, and 1,3,6-hexane trinitrile in ethylene glycol bis(propionitrile) ether, the generation of gas at high temperature of the lithium-ion battery is further reduced, and the high-rate discharge performance is further improved.
[0138] It is to be understood that the present application is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present application. In addition, under the guidance of the present application, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the scope of the present application. Therefore, the present application is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present application.
Claims
1. A secondary battery, It is characterized in that The secondary battery comprises a positive electrode, a negative electrode, a separator and an electrolyte; The negative electrode comprises a negative electrode active material layer, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises a silicon-carbon material; The electrolyte comprises ethyl propionate and propyl propionate, and based on the total mass of the electrolyte, the mass percentage of the ethyl propionate is a%, and the mass percentage of the propyl propionate is b%, wherein 1.7≤a / b≤5.7; The electrolyte further comprises at least one of vinylene carbonate, boron-containing lithium salt, and a compound having the structural formula shown in Formula I; Wherein, in formula I, A is selected from C 2 To C 5 of alkylene; The electrolyte further includes at least two of 1,3-propane sultone, succinonitrile, ethylene glycol bis(propionitrile) ether, and 1,3,6-hexanetrinitrile.
2. The secondary battery according to claim 1, It is characterized in that Based on the total mass of the electrolyte, the mass percentage ratio of the ethyl propionate to the propyl propionate is in the range of 3.1≤a / b≤4.
9.
3. The secondary battery according to claim 1, It is characterized in that Based on the total mass of the electrolyte, the mass percentage range of the ethyl propionate is: 20%≤a≤70%; or, based on the total mass of the electrolyte, the mass percentage range of the ethyl propionate is: 36%≤a≤54%; or, based on the total mass of the electrolyte, the mass percentage range of the ethyl propionate is: 20%≤a≤30%.
4. The secondary battery according to claim 1, It is characterized in that Based on the total mass of the electrolyte, the mass percentage content of the propyl propionate ranges from 11%≤b≤20%; or, based on the total mass of the electrolyte, the mass percentage content of the propyl propionate ranges from 11%≤b≤15%.
5. The secondary battery according to claim 1, It is characterized in that Based on the total mass of the electrolyte, the sum of the mass percentages of the ethyl propionate and the propyl propionate is in the range of 32%≤a+b≤84%; or, based on the total mass of the electrolyte, the sum of the mass percentages of the ethyl propionate and the propyl propionate is in the range of 47%≤a+b≤65%.
6. The secondary battery according to claim 1, It is characterized in that The compound having the structural formula represented by Formula I satisfies at least one of the conditions (1) to (2): (1) Based on the total mass of the electrolyte, the mass percentage of the compound containing the structural formula represented by Formula I is 0.11% to 4.9%; (2) The compound having the structure represented by Formula I includes the compound having the structure represented by Formula II:
7. The secondary battery according to claim 1, It is characterized in that The electrolyte satisfies at least one of the conditions (3) to (4): (3) The electrolyte contains vinylene carbonate, and the mass percentage of the vinylene carbonate is 0.01% to 0.3% based on the total mass of the electrolyte; (4) The electrolyte contains vinylene carbonate and boron-containing lithium salt, and the sum of the mass percentages of vinylene carbonate and boron-containing lithium salt is 0.04% to 0.2% based on the total mass of the electrolyte.
8. The secondary battery according to claim 1, It is characterized in that The boron-containing lithium salt satisfies at least one of the conditions (5) to (6): (5) The mass percentage of the boron-containing lithium salt is 0.01% to 0.25%; (6) The boron-containing lithium salt is selected from at least one of lithium difluorooxalatoborate, lithium tetrafluoroborate, and lithium borate.
9. The secondary battery according to claim 1, It is characterized in that The electrolyte further includes at least one of fluoroethylene carbonate, propylene carbonate, and ethylene carbonate.
10. The secondary battery according to claim 9, It is characterized in that The electrolyte satisfies at least one of the conditions (7) to (9): (7) The electrolyte contains fluoroethylene carbonate, and the mass percentage of the fluoroethylene carbonate is 2% to 7% based on the total mass of the electrolyte; or the mass percentage of the fluoroethylene carbonate is 2% to 5% based on the total mass of the electrolyte; (8) The electrolyte contains propylene carbonate, and the mass percentage of the propylene carbonate is 20% to 40% based on the total mass of the electrolyte; or the mass percentage of the propylene carbonate is 20% to 30% based on the total mass of the electrolyte; (9) The electrolyte contains ethylene carbonate, and the mass percentage of the ethylene carbonate is 4% to 18% based on the total mass of the electrolyte; or, the mass percentage of the ethylene carbonate is 5% to 18% based on the total mass of the electrolyte; or, the mass percentage of the ethylene carbonate is 10% to 18% based on the total mass of the electrolyte.
11. The secondary battery according to claim 1, It is characterized in that The electrolyte satisfies at least one of the conditions (10) to (13): (10) The electrolyte contains 1,3-propane sultone, and the mass percentage of the 1,3-propane sultone is 0.1% to 4% based on the total mass of the electrolyte; or, based on the total mass of the electrolyte, the mass percentage of the 1,3-propane sultone is 0.8% to 3.1%; or, based on the total mass of the electrolyte, the mass percentage of the 1,3-propane sultone is 1.2% to 2.4%; (11) The electrolyte contains succinonitrile, and the mass percentage of succinonitrile is 0.1% to 4% based on the total mass of the electrolyte; or, the mass percentage of succinonitrile is 0.2% to 2.5% based on the total mass of the electrolyte; or, the mass percentage of 1,3-propane sultone is 1.6% to 2.4% based on the total mass of the electrolyte; (12) The electrolyte contains ethylene glycol bis(propionitrile) ether, and the mass percentage of ethylene glycol bis(propionitrile) ether is 0.01% to 1% based on the total mass of the electrolyte; or, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis(propionitrile) ether is 0.1% to 0.8%; or, based on the total mass of the electrolyte, the mass percentage of ethylene glycol bis(propionitrile) ether is 0.5% to 0.8%; (13) The electrolyte contains 1,3,6-hexanetrinitrile, and the mass percentage of 1,3,6-hexanetrinitrile is 0.1% to 3.5% based on the total mass of the electrolyte; or, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexanetrinitrile is 0.2% to 2.5%; or, based on the total mass of the electrolyte, the mass percentage of 1,3,6-hexanetrinitrile is 1.3% to 2.2%.
12. The secondary battery according to claim 1, It is characterized in that The silicon-carbon material accounts for 1% to 15% by mass of the negative electrode active material.
13. An electronic device, It is characterized in that The electronic device comprises the secondary battery according to any one of claims 1 to 12.
